Trust and fake news: exploratory analysis of the impact of news literacy on the relationship with news content in Portugal - Paisana, M. (2020)
In order to understand the role of contemporary journalism and the media system it is vital to consider consumers’ relationship with news content in terms of trust and perception of dubious content. This analysis is particularly relevant in a context where intense flows of information raise serious questions about individual ability to interpret, validate, and reproduce content. This analysis explores a news literacy scale used by Maskl et al. (2015) and Fletcher (in Newman et al., 2018) to investigate the links between news literacy profiles and their relationship with content, with particular focus on illegitimate/doubtful news pieces. Results suggest individuals with higher news literacy tend to trust news in general but not when content originates in social media. Higher literacy profiles are also associated with increased concern regarding online content legitimacy. These conclusions are particularly relevant in the currently volatile media sphere, highly dependent on a substantially informed public to ensure the legitimacy and importance of journalistic content and to distinguish it from other kinds of content flooding communication networks. These efforts depend not only on the journalistic sphere but also on democratic systems themselves as they rely on a well-informed public to guarantee a healthy and inclusive debate.